Targeting radiotherapy-induced inflammation in cancer metastasis: insights into immune modulation, therapeutic opportunities and radiogenomics - Lee, Ee Qian; Looi, Chin-King; Tan, Lu Ping; Chew, Yik Ling; Lim, Wei-Meng; Foong, Lian-Chee; Leong, Chee-Onn; Cheong, Kok Whye; Mai, Chun-Wai (Frontiers in Oncology, 2025)
Radiotherapy (RT) is the first-line treatment for more than 50% of newly diagnosed cancer patients and remains a cornerstone of cancer therapy, particularly for tumors that are inoperable, recurrent, or incompletely resected. Despite advancements in RT techniques, locoregional recurrence and distant metastasis remain critical clinical challenges, contributing significantly to cancer-related inflammation and mortality. Emerging evidence suggests that RT may inadvertently promote metastasis through inflammation-related immune modulations, such as the dysregulation of signaling cascades, such as focal adhesion kinase (FAK), phosphoinositide 3-kinases (PI3K)/protein kinase B (AKT), p38 mitogen-activated protein kinase (p38 MAPK), and nuclear factor-kappa B (NF-κB) signaling cascades. Targeting these pro-metastatic pathways using specific inflammatory inhibitors and clinically available repurposed drugs has shown promise in numerous preclinical models, offering a rational approach to mitigate radiation-induced inflammation in metastatic progression. With the rapid advancements of high-throughput sequencing and medical imaging technologies, radiogenomics, which incorporates medical imaging and genomic data, offers great promise for cancer diagnosis, tumor classification, treatment selection, and disease monitoring through the identification of predictive and prognostic biomarkers. This review critically unravels the immune modulation underlying radiation-induced inflammation in cancer metastasis and highlights the need for comprehensive studies combining radiogenomics with RT and targeted therapies. Such approaches hold potential to improve therapeutic outcomes and reduce metastatic burden, paving the way for more effective and personalized cancer treatments.